2023
DOI: 10.1038/s42003-023-04691-8
|View full text |Cite
|
Sign up to set email alerts
|

The circadian clock in the piriform cortex intrinsically tunes daily changes of odor-evoked neural activity

Abstract: The daily activity in the brain is typically fine-tuned by the circadian clock in the local neurons as well as by the master circadian clock in the suprachiasmatic nucleus (SCN) of the hypothalamus. In the olfactory response, odor-evoked activity in the piriform cortex (PC) and olfactory behavior retain circadian rhythmicity in the absence of the SCN, yet how the circadian rhythm in the PC is achieved independently of the SCN remains elusive. Here, to define neurons regulating the circadian rhythm of the odor-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…In each case, this rhythmicity is entrained by external cues, and, in turn, the rhythmic signals produced in each area project to downstream regions to provide an entraining signal ( Hastings et al, 1998 ; Granados-Fuentes et al, 2004a , 2006 ; Nolasco et al, 2012 ; Saper, 2013 ). The entraining signals provided by each of these systems have significant implications for behavior, and the rhythms that they provide have been found to be negatively impacted in AD, particularly in the case of the circadian system ( Granados-Fuentes et al, 2011 ; Saper, 2013 ; Musiek et al, 2018 ; Takeuchi et al, 2023 ). Synchrony of rhythmicity within the cells of the SCN and OB is dependent on the neuropeptide VIP, which is a potential shared target by mechanisms of AD ( Aton et al, 2005 ; Oddo, 2012 ; Miller et al, 2014 ; Liu et al, 2018 ; Todd et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, this rhythmicity is entrained by external cues, and, in turn, the rhythmic signals produced in each area project to downstream regions to provide an entraining signal ( Hastings et al, 1998 ; Granados-Fuentes et al, 2004a , 2006 ; Nolasco et al, 2012 ; Saper, 2013 ). The entraining signals provided by each of these systems have significant implications for behavior, and the rhythms that they provide have been found to be negatively impacted in AD, particularly in the case of the circadian system ( Granados-Fuentes et al, 2011 ; Saper, 2013 ; Musiek et al, 2018 ; Takeuchi et al, 2023 ). Synchrony of rhythmicity within the cells of the SCN and OB is dependent on the neuropeptide VIP, which is a potential shared target by mechanisms of AD ( Aton et al, 2005 ; Oddo, 2012 ; Miller et al, 2014 ; Liu et al, 2018 ; Todd et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also similar to the SCN, the OB appears to receive entraining signals that can act as zeitgebers from structures aside from the SCN ( Nolasco et al, 2012 ). It is unclear how the OB sends synchronizing signals to structures peripheral to it, but it has been shown that it communicates such signals to downstream olfactory structures, namely the piriform cortex ( Granados-Fuentes et al, 2006 ; Takeuchi et al, 2023 ). Studies of mice have demonstrated that these rhythms are not merely incidental and have significant behavioral implications for olfactory sensitivity and discrimination, as measured by neural activity and behavior, as well as more complex behavioral tasks requiring olfaction ( Nordin et al, 2003 ; Granados-Fuentes et al, 2011 ; Pantazopoulos et al, 2011 ; Takeuchi et al, 2023 ).…”
Section: Functional Similarities Of Circadian and Olfactory Systemsmentioning
confidence: 99%
“… Granados-Fuentes et al (2011) reported that the SCN lesion altered the peak phases of the daily rhythm of olfactory discrimination performance ( Granados-Fuentes et al, 2011 ). In addition, Takeuchi et al reported in 2023 that knockout of Bmal1 in Vgat-positive neurons, including SCN neurons, altered the peak phase of the circadian rhythm of odor-induced c-fos positive cell number in the piriform cortex ( Takeuchi et al, 2023 ). These results indicate that the SCN alters the peak phase of olfactory function, suggesting that it contributes to the synchronization of the circadian rhythms of olfactory function and the central clock.…”
Section: Olfaction and Circadian Rhythmsmentioning
confidence: 99%
“… Granados-Fuentes et al (2011) reported that there is a daily rhythm in the performance and sensitivity of the odor detection task that disappears when the clock genes Bmal1 or both Per1 and Per2 genes are knocked out ( Granados-Fuentes et al, 2011 ). Takeuchi et al report that Bmal1 knockout in the piriform cortex abolishes the circadian rhythm of the odor-evoked activity ( Takeuchi et al, 2023 ). Using quantitative PCR, they report that the circadian rhythm of gene expression observed in the piriform cortex is dependent on Bmal1 expression in Emx-positive cells, including pyramidal cells in the piriform cortex ( Takeuchi et al, 2023 ).…”
Section: Olfaction and Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation